Phylogenetic analysis for endemic Fritillaria baskilensis Behçet (Liliaceae): Evidence from cpDNA “trn” sequences - Sancar, Pelin Yılmaz; Taskin, Irmak Icen; Kurşat, Murat; Munzuroğlu, Ömer (My University, 2021)
Fritillaria baskilensis Behçet., which was first collected from Elazig - Baskil district in 1998 and introduced to \rthe scientific world as a new species, is one of Turkey's endemic inverted tulip species. This study aims to determine the \rsystematic relationships between Fritillaria baskilensis and other Fritillaria species using molecular techniques. Also; \rAs a result of this study, we tried to determine for the first time in which subgenus the endemic species in question will \rtake place.\rAfter the DNA isolation with the CTAB method, the trnT-trnL3' region of 5 samples was amplified by using \rtrna and trnd primers, and a total of 27 Fritillaria species were analyzed together with 2 outgroups in the MEGA \rprogram, together with other sequence information obtained from NCBI. While our analyzes are consistent with the \rliterature, the fact that Fritillaria baskilensis is in the same branch as members of the subgenus Fritillaria suggests that \rF. baskilensis is included in this subgenus.\rThis study is very important as it is the first molecular-based study using sequence information from Fritillaria \rbaskilensis populations, and the new “trn” gene region haplotypes of the mentioned species were determined by us for \rthe first time and added to the GenBank database
Keywords: Biyoloji; Ekoloji; Genetik ve Kalıtım; Biyoloji Çeşitliliğinin Korunması